DARI HYPE KE CHECKOUT: FOMO SEBAGAI JEMBATAN ANTARA INFLUENCER, ULASAN PELANGGAN, DAN PEMBELIAN PRODUK RUCAS SPORTSWEAR - Agnes, Agnes; Setiawan, Harry; Afifah, Nur; Purmono, Bintoro Bagus (SINERGI : Jurnal Riset Ilmiah, 2025)
Rucas Sportswear has successfully optimized its Fear of Missing Out (FOMO)-based marketing strategy to increase its consumer appeal. This study explores the role of FOMO as a mediator in the relationship between Influencer Marketing, Customer Reviews (e-WOM), and Rucas Sportswear Product Purchase Decisions. Through a quantitative approach using the PLS-SEM method, data was collected from consumers who actively participated in the promotions and reviews of these products on digital platforms. This study uncovers how influencer endorsement strategies and customer testimonials can shape the psychological urgency that drives spontaneous buying behaviour. The results of this study are expected to provide insight into the effectiveness of FOMO-based digital marketing in increasing sales conversions in the sports apparel industry. The results of this study show that there is a significant positive relationship between influencer marketing and customer reviews on purchase decisions, through FOMO as a psychological bridge that strengthens the effects of both. Marketing strategies that trigger FOMO have proven to be effective in creating a sense of urgency and consumer engagement, thereby driving purchase intent more quickly and emotionally.